Color Vision Losses in Autism Spectrum Disorders - Zachi, Elaine C.; Costa, Thiago L.; Barboni, Mirella T. S.; Costa, Marcelo F.; Bonci, Daniela M. O.; Ventura, Dora F. (Frontiers in Psychology, 2017)
Autism spectrum disorders (ASDs) are neurodevelopmental conditions characterized by impairments in social/communication abilities and restricted behaviors. The present study aims to examine color vision discrimination in ASD children and adolescents without intellectual disability. The participants were also subdivided in order to compare color vision thresholds of autistic participants and those who achieved diagnostic criteria for Asperger Syndrome (AS). Nine subjects with autism, 11 participants with AS and 36 typically developing children and adolescents participated in the study. Color vision was assessed by the Cambridge Colour Test (CCT). The Trivector protocol was administered to determine color discrimination thresholds along the protan, deutan and tritan color confusion lines. Data from ASD participants were compared to tolerance limits for 90% of the population with 90% probability obtained from controls thresholds. Of the 20 ASD individuals examined, 6 (30%) showed color vision losses. Elevated color discrimination thresholds were found in 3/9 participants with autism and in 3/11 AS participants. Diffuse and tritan deficits were found. Mechanisms for chromatic losses may be either at the retinal level and/or reflect reduced cortical integration.